Learning behavior-driven development with JavaScript create powerful yet simple-to-code BDD test suites in JavaScript using the most popular tools in the community - Amodeo, Enrique (Packt Publishing, 2015)
This book is ideal for any JavaScript developer who is interested in producing well-tested code. If you have no prior experience with testing, Node.js, or any other tool, do not worry, as they will be explained from scratch.
Includes index. - Description based on online resource; title from cover (Safari, viewed March 13, 2015)
Keywords: JavaScript (Computer program language); Application software -- Development; JavaScript (Langage de programmation); Logiciels d'application; Développement; Application software; Development